Perbaikan Proses Bisnis Pembangunan Base Transceiver Station (BTS) Menggunakan Business Process Improvement (Studi Kasus: Badan Aksesibilitas Telekomunikasi dan Informasi KOMINFO) - Salsabilla Syafta; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
BAKTI KOMINFO is an organization that engaged in telecommunications and information. This organization has several priority programs that aim to provide broader access to 3T areas, namely Remote, Outermost, and Disadvantaged areas. One of the priority programs is the construction of the Base Transceiver Station (BTS) which is under the auspices of Infrastructure Directorate. In its implementation, there is quite common obstacle, which is miscommunication between the parties involved. Therefore it is necessary to analyze and evaluate business processes to find the root of the problem and make recommendations for improving the business processes. In this study, the Business Process Model and Notation (BPMN) is used to conduct business process modeling, the Five Whys Analysis method is used to evaluate business processes, and the Business Process Improvement (BPI) method is used to improve business processes. Based on the results of simulations on current business process and business process recommendations, there found the acceleration of duration up to 17.54% in the BTS business process and 34.67% in the Procurement (e-Purchasing) business process. The business process recommendations can also minimize the occurrence of problems, so it can be concluded that the business process recommendations can make the running of the current business processes better.